Influence of poly(ethylene grycol) - (PEG) on the properties of influence of poly(3-hydroxybutyrate-CO-3-hydroxyvalerate) - PHBV - Sara E. M. Catoni; Ketlyn N. Trindade; Caio A. T. Gomes; Andréa L. S. Schneider; Ana P.T. Pezzin; Valdir Soldi (Polímeros, 2013)
Films of poly(3-hydroxybutyrate-co-3-hydroxyvalerate) - PHBV with polyethylene glycol (PEG) were prepared by casting solvent evaporation. The thermal behavior, morphology, crystallinity and molecular weight of these films were studied by the following techniques: differential scanning calorimetry (DSC), scanning electron microscopy (SEM), X-ray diffraction (XRD), size exclusion chromatography (SEC). Mixtures of PHBV/PEG showed a high crystallinity degree, measured by XRD, with values ranging between 60 and 90% according to the concentration of PEG. The melting temperature of PHBV decreased with increasing addition of plasticizer (PEG) in the mixture. SEM results showed that the mixtures were uniform, except for the composition 50/50 which proved to be heterogeneous, as evidenced by the presence of two phases. PHBV had molar mass (Mw = 206000 g mol-1), while the introduced PEG molar mass (Mw = 1350 to 1650 g mol-1). The addition of PEG caused the crystallinity of the polymer films to increase owing to the high crystallinity of PEG. The melting point of the PHBV/PEG mixtures also diminished. In addition, SEC analysis of the blends indicated a reduced molar mass for the mixtures in comparison to pure PHBV (100/0).